PENERAPAN GOOD CORPORATE GOVERNANCE: PENDEKATAN TEORI RISET AKUNTANSI PADA PERUSAHAAN PERBANKAN DI INDONESIA - Hendrarto Widodo (Accounting Journal of Ibrahimy (AJI), 2023)
Based on the application phenomenon and the rules issued by regulatory agency related Good Coporate Governance (GCG), there fore many researchers conduct research on the basis for agency theory and sterwarship theory. As a theoretical for research. Tha purpose of this research is to see whether the research uses a basic theoretical approach using agency theory, sterwarship theory or a combination of two theories, this research method is a qualitative discriminatory collection ofemrical research journal data relating to agency theory and sterwarship theory carried out via the internet on the web gogel cendikia, from result of observers there are eleven emprical studies using agency theory while one study combines the two theories as a research basic.meaning that it can be cpncluded that agency theory is agency theory as a thepretical basis in research related to the implementation of Good Coporate Governance with accounting practic